Bioaktivitas Ekstrak Daun Namnam (Cynometra cauliflora L.) Terhadap Antidiabetes Secara In Vitro - Anliza, Syarah; Rachmawati, Nurmeily (Jambura Journal of Chemistry, 2024)
Every day our bodies produce free radicals and every organism has a natural defense system to reduce free radicals. In a healthy state the amount of antioxidants in the body can balancing the amount of free radicals. However, in certain circumstances it can interfere with the body's defense against free radicals. This situation underlies the occurrence of various diseases caused by radicals, one of which is non-communicable (degenerative) diseases. Many therapies are available for the treatment of diabetes, do not completely cure the disease but cause many side effects. Namnam plant is predict to have the ability as an anti-diabetic agent. The purpose of this study was to determine the in vitro bioactivity of Namnam leaves extract against antidiabetic. This research conducted extraction, phytochemical test, total phenol test, total flavonoid test, and in vitro -glucosidase enzyme inhibition test as an antidiabetic. The results of the study showed that the ethanol extract produced secondary metabolites, namely flavonoids and steroids. The results of the Î±-glucosidase inhibition test resulted in an IC50 value of 30,89 ppm. The comparison that has been used is acarbose which produces IC50 of 0.22 ppm. Ethanol extract and ethyl acetate extract have inhibitory ability due to the presence of flavonoid and steroid compounds contained in the extract